2020
DOI: 10.1016/j.ygyno.2019.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel lymph node mapping alone compared to more extensive lymphadenectomy in patients with uterine serous carcinoma

Abstract: h i g h l i g h t s Systematic LND showed no survival benefit vs SLN mapping alone in patients with USC. Detection of nodal metastasis is the same in SLN mapping alone vs systematic LND.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 21 publications
(27 reference statements)
0
21
0
Order By: Relevance
“…A total of 2,048 articles were screened through the search strategy, and 21 articles were included after full text reading. Four were excluded for low quality assessment score (<6) ( 14 17 ), two were excluded for patients overlapping ( 18 , 19 ), thus leaving 15 articles eligible for final analysis ( 7 , 20 33 ) ( Figure 1 ). Characteristics of the 15 studies are summarized in Supplement Table S1 .…”
Section: Resultsmentioning
confidence: 99%
“…A total of 2,048 articles were screened through the search strategy, and 21 articles were included after full text reading. Four were excluded for low quality assessment score (<6) ( 14 17 ), two were excluded for patients overlapping ( 18 , 19 ), thus leaving 15 articles eligible for final analysis ( 7 , 20 33 ) ( Figure 1 ). Characteristics of the 15 studies are summarized in Supplement Table S1 .…”
Section: Resultsmentioning
confidence: 99%
“…The same histology type was further and thoroughly reviewed by MSKCC in a recent paper published by Basaran et al. ( 118 ). This time, they carefully categorized uterine serous carcinoma patients in January 1996 to December 31, 2017 into SLN only group (79) and LAD without SLN group (166).…”
Section: The Application Of Slnm In Early-stage High-risk Ecmentioning
confidence: 99%
“…Although randomized data supporting this approach are lacking, the rarity of this disease makes accrual to clinical trials challenging. Meanwhile, the relatively high rate of DM despite the use of aggressive adjuvant therapy, even in patients with early-stage disease, highlights the need for additional advances for these patients, such as improved surgical techniques 27 and the use of targeted agents like trastuzumab. 28 Finally, inclusion of these patients in larger randomized trials for endometrial cancer is needed, as has been previously suggested, 29 to help improve treatment strategies for this aggressive disease.…”
Section: Discussionmentioning
confidence: 99%